Excessive Loss of Skeletal Muscle Mass in Older Adults With Type 2 Diabetes - Park, Seok Won; Goodpaster, Bret H; Lee, Jung Sun; Kuller, Lewis H; Boudreau, Robert; de Rekeneire, Nathalie; Harris, Tamara B; Kritchevsky, Stephen; Tylavsky, Frances A; Nevitt, Michael; Cho, Yong-wook; Newman, Anne B (Diabetes care, 2009)
OBJECTIVE: A loss of skeletal muscle mass is frequently observed in older adults. The aim of the study was to investigate the impact of type 2 diabetes on the changes in body composition, with particular interest in the skeletal muscle mass. RESEARCH DESIGN AND METHODS: We examined total body composition with dual-energy X-ray absorptiometry annually for 6 years in 2,675 older adults. We also measured mid-thigh muscle cross-sectional area (CSA) with computed tomography in year 1 and year 6. At baseline, 75-g oral glucose challenge tests were performed. Diagnosed diabetes (n = 402, 15.0%) was identified by self-report or use of hypoglycemic agents. Undiagnosed diabetes (n = 226, 8.4%) was defined by fasting plasma glucose (greater-than-or-equal7 mmol/l) or 2-h postchallenge plasma glucose (greater-than-or-equal11.1 mmol/l). Longitudinal regression models were fit to examine the effect of diabetes on the changes in body composition variables. RESULTS: Older adults with either diagnosed or undiagnosed type 2 diabetes showed excessive loss of appendicular lean mass and trunk fat mass compared with nondiabetic subjects. Thigh muscle CSA declined two times faster in older women with diabetes than their nondiabetic counterparts. These findings remained significant after adjusting for age, sex, race, clinic site, baseline BMI, weight change intention, and actual weight changes over time. CONCLUSIONS: Type 2 diabetes is associated with excessive loss of skeletal muscle and trunk fat mass in community-dwelling older adults. Older women with type 2 diabetes are at especially high risk for loss of skeletal muscle mass.